Propuesta de normativo técnico basado en el estándar ANSI/TIA 570 para el diseño e implementación de redes de cableado estructurado en residencias tipo del cantón Loja. - Fernández Iñiguez, Danny Alfredo (2020)
The present work of investigation and creation of technical normative was done based on the evident necessity of a guided document for the planning and installation of the structural wiring of the type of housing of Loja City. This based on the revision of the literature, field studies, interviews and election of methodology. Determining this way recommendations for the structure of the normative. Every single process followed were fundamental for the development of conclusions and recommendations according to the subject and the goals planned. Based on the revision of the literature, information was gathered about the actual estate of the planning of the residential wiring of the type of housing of Loja City and as well an investigation was conducted about the valid international standards about the residential wiring and based on the collected information establish the right directions to follow in order to elaborate the document. With the methodological process planted we arrived to the realization of technical normative based into the goals and as well the exemplification of the recommendations generated in this document like the creation of a distribution center based on the software Google SketchUp keeping in mind each one of the sections mentioned in the normative. Also based in this we were able to make a referential design of the location and wiring of the different telecommunication services specified in a plan using the software tool Google SketchUP.